Lifetime Prevalence of Abortion and Risk Factors in Women: Evidence from a Cohort Study. (27th April 2020) - Moradinazar, Mehdi; Najafi, Farid; Nazar, Zeinab Moradi; Hamzeh, Behrooz; Pasdar, Yahya; Shakiba, Ebrahim
Abstract : Background . 10-20% of pregnancies end due to spontaneous abortions. In recent years, nondocumentary evidence has been indicative of an increase in the prevalence of nonspontaneous abortions in Iran, especially in the Kurdish regions. The aim of this study is to assess the lifetime prevalence of spontaneous abortions and factors affecting spontaneous abortion in women 35-65 years old. Method . Data from the recruitment phase of Ravansar Non-Communicable Disease (RaNCD) cohort study was used. All of the 4831 married women 35-65 years old and with history of pregnancy were included in this study. In order to determine the abortion ratio, the number of abortions was divided by the number of live births, and multiple logistic regression analysis was applied to determine associated factors affecting abortion. Results . About 25.7% of women had a history of spontaneous abortion. The abortion ratio in women was 0.10. The abortion ratio in women with secondary education, first pregnancy and marriage age at ≥26, socioeconomic condition, and hyperthyroid and diabetes was high while the abortion ratio of women with high physical activity and BMI < 18.9 or residents of rural area was low. After assessing the effective variables, it was found that women with high blood pressure have 63% less odds for nonspontaneous abortion, which is statistically significant (p value < 0.05 ). Conclusion . Considering the effect of factors such as level of education, older age at the first marriage, and age at the first pregnancy on increased chance of spontaneous abortion, measures should be taken to take more care for these people.